Results of a Phase II Study to Determine the Efficacy and Safety of Genetically Engineered Allogeneic Human Chondrocytes Expressing TGF-β1 - Lee, Bumsup; Parvizi, Javad; Bramlet, Dale; Romness, David W.; Guermazi, Ali; Noh, Moon; Sodhi, Nipun; Khlopas, Anton; Mont, Michael A. (The Journal of Knee Surgery, 2020)
Genetically engineered chondrocytes virally transduced with a transforming growth factor (TGF)-β1 (TG-C [TissueGene-C]) expression vector have been shown to have potential benefits in the nonoperative management of knee osteoarthritis. Previous literature has reported on safe dosages of TG-C. Therefore, the purpose of this study was to evaluate the Phase II results and a 24-month efficacy of this injectable mixture compared with placebo in patients with Kellgren–Lawrence (K–L) grade III knee osteoarthritis. Specifically, we assessed (1) functional outcomes, (2) pain scores, (3) adverse events (AEs), and (4) magnetic resonance imaging (MRIs) findings. We performed a multicenter, double-blinded, placebo-controlled, and randomized study of adults who had K–L grade III knee osteoarthritis. A total of 102 patients were 2:1 randomized to TG-C at a dose of 3.0 × 107 cells, or placebo injections between May 1, 2011 and October 31, 2012. Outcomes analyzed were knee joint function, pain, quality of life, adverse events, and MRI findings using the whole-organ magnetic resonance imaging score (WORMS) system. There were significant improvements in the International Knee Documentation Committee (IKDC) and visual analogue scale (VAS) scores in the TG-C cohort, when compared with the placebo cohort at weeks 12, 52, 72, and 104 (p < 0.05). No severe AEs were observed. Common AEs were arthralgia, joint inflammation, and joint effusion which were similar between both cohorts. Whole-knee MRIs at 12 months showed less progression of cartilage damage, infrapatellar fat pad-synovitis, and effusion-synovitis in the TG-C cohort. Patients who received TG-C had significant improvements in IKDC and VAS scores. These patients also reported less severe and frequent pain. Additionally, fewer patients treated with TG-C showed progression of cartilage damage, as well as less progression of infrapatellar fat pad synovitis and effusion-synovitis. Furthermore, treatment with TG-C was generally well tolerated with minor AEs. Therefore, based on these results, TG-C appears to be a safe and effective modality for the management of K–L grade III osteoarthritis.
Keywords: genetically modified; growth factors; knee; osteoarthritis; pain